PENGARUH FAKTOR INTERNAL, MAKROEKONOMI, DAN KONSENTRASI PANGSA PASAR TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL DI INDONESIA PERIODE 2012-2016 - OKTAVIA ZAMAN, CAHYANI; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to analyze the influence of internal factors, macroeconomics, and market concentration on profitability at conventional banks in Indonesia period 2012-2016. Profitability that is proxied by Return On Assets ( ROA) is influenced by internal factors that is Capital Adequacy Ratio (CAR), credit risk, liquidity and size. Macroeconomic variables are inflation, interest rate, and market concentration. This study used multiple linear regression analysis with SPSS program for data analysis technique. The data used are secondary data obtained from official website of the bank Indonesia and each bank. The sample used in this study are conventional banks which publishes financial statements during the study period 2012-2016. The results of this research indicated that partially size and market concentration has no influence on profitability. CAR, liquidity, and inflation has a positive affect on profitability. Credit risk and interest rate has a negative affect on profitability. Keywords: Capital Adequacy Ratio, Credit Risk, Inflation, Market Concentration, Profitability.